Study of Religion in Southern Africa, Essays in Honour of G.C. Oosthuizen. - Johannes Smit; Pratap Kumar (Editors) (Numen Book Series, 2005)
This collection of essays is brought together in the honour of Gerhardus Cornelis (Pippin) Oosthuizen on his eighty third birthday. Pippin has been one of the most significant religion researchers and prolific Humanities publishers South Africa has ever produced. Among his friends and colleagues are some of the most important scholars of religion in South Africa and elsewhere. With his critical acumen and insightful understanding of the ebb and flow of the South African socio-political landscape of the last fifty-odd years, he has been a distinguished leader in research and has been honoured with Honorary doctorates from South Africa's leading universities. This collection constitutes a small token of appreciation for his more than fifty years in academia and his academic leadership.